Hepatic ketone body regulation of renal gluconeogenesis - Ryo Hatano; Eunyoung Lee; Hiromi Sato; Masahiro Kiuchi; Kiyoshi Hirahara; Yoshimi Nakagawa; Hitoshi Shimano; Toshinori Nakayama; Tomoaki Tanaka; Takashi Miki (Elsevier, 2024)
Objectives: During fasting, liver pivotally regulates blood glucose levels through glycogenolysis and gluconeogenesis. Kidney also produces glucose through gluconeogenesis. Gluconeogenic genes are transactivated by fasting, but their expression patterns are chronologically different between the two organs. We find that renal gluconeogenic gene expressions are positively correlated with the blood β-hydroxybutyrate concentration. Thus, we herein aim to investigate the regulatory mechanism and its physiological implications. Methods: Gluconeogenic gene expressions in liver and kidney were examined in hyperketogenic mice such as high-fat diet (HFD)-fed and ketogenic diet-fed mice, and in hypoketogenic PPARα knockout (PPARα−/−) mice. Renal gluconeogenesis was evaluated by rise in glycemia after glutamine loading in vivo. Functional roles of β-hydroxybutyrate in the regulation of renal gluconeogenesis were investigated by metabolome analysis and RNA-seq analysis of proximal tubule cells. Results: Renal gluconeogenic genes were transactivated concurrently with blood β-hydroxybutyrate uprise under ketogenic states, but the increase was blunted in hypoketogenic PPARα−/− mice. Administration of 1,3-butandiol, a ketone diester, transactivated renal gluconeogenic gene expression in fasted PPARα−/− mice. In addition, HFD-fed mice showed fasting hyperglycemia along with upregulated renal gluconeogenic gene expression, which was blunted in HFD-fed PPARα−/− mice. In vitro experiments and metabolome analysis in renal tubular cells showed that β-hydroxybutyrate directly promotes glucose and NH3 production through transactivating gluconeogenic genes. In addition, RNA-seq analysis revealed that β-hydroxybutyrate-induced transactivation of Pck1 was mediated by C/EBPβ. Conclusions: Our findings demonstrate that β-hydroxybutyrate mediates hepato-renal interaction to maintain homeostatic regulation of blood glucose and systemic acid-base balance through renal gluconeogenesis regulation.